2017
DOI: 10.1038/srep46260
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic bead-in-droplet ejection utilizing an integrated plug-in bead dispenser for single bead–based applications

Abstract: This paper presents a deterministic bead-in-droplet ejection (BIDE) technique that regulates the precise distribution of microbeads in an ejected droplet. The deterministic BIDE was realized through the effective integration of a microfluidic single-particle handling technique with a liquid dispensing system. The integrated bead dispenser facilitates the transfer of the desired number of beads into a dispensing volume and the on-demand ejection of bead-encapsulated droplets. Single bead–encapsulated droplets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Streule et al reported a device, named single-cell-manipulator (SCM), with a separable piezo-stack actuator [14]. Choi et al [15] and Kim et al [16] developed a novel nanoliter liquid dispensing system with plug-and-play dispensers and detachable pneumatic pump. Furthermore, Bsoul et al presented a disposable ink-jet dispenser technology and demonstrated a Lab-on-a-printer concept through using an ink-jet dispenser and a microfluidic mixer [17].…”
Section: Journal Of Micromechanics and Microengineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Streule et al reported a device, named single-cell-manipulator (SCM), with a separable piezo-stack actuator [14]. Choi et al [15] and Kim et al [16] developed a novel nanoliter liquid dispensing system with plug-and-play dispensers and detachable pneumatic pump. Furthermore, Bsoul et al presented a disposable ink-jet dispenser technology and demonstrated a Lab-on-a-printer concept through using an ink-jet dispenser and a microfluidic mixer [17].…”
Section: Journal Of Micromechanics and Microengineeringmentioning
confidence: 99%
“…Furthermore, a multiplexed, scalable, and compact microfluidic multi-parametric gradient generation system based on MIP was developed for multi-dimensional studies of synthetic genetic modules in cell-free system [19]. Different from those of previously mentioned nano-liter dispensing technologies [15][16][17], the refill of liquid in the MIP system is conducted automatically by the combined effect of capillary force in the microchannel and negative pressure generated by the membrane's deformation restoration, which means it does not need any additional input from an external pump or potential energy. With the design of microfluidic channel and nozzle, the minimum loading volume and dead volume of the MIP system are as low as 2 μl and 0.25 μl, respectively [19].…”
Section: Journal Of Micromechanics and Microengineeringmentioning
confidence: 99%
“…It enables placing the microparticles one by one into an arbitrary location simply on the basis of flow resistance [ 11 ]. Until now, this method has been widely used to immobilize droplets or cells, meaning that it would be beneficial to a variety of applications [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Taking this into account, it is conceivable that, in combination with the hydrodynamic trapping technique, developing new microscale fluorescent materials or microscale carriers for encapsulating conventional fluorescent reagents should be a key to addressing the problem of the dimensional gap.…”
Section: Introductionmentioning
confidence: 99%
“…Bead-based assays have been widely used in disease diagnostic, biological, and chemical analysis because of their high flexibility in usage. For example, they can be integrated with microfluidic chips, optical fibers, microwells, and tips. The surface of bead can be easily functionalized with various biorecognition receptors, such as antibody, molecular imprint, aptamer, and peptide. Therefore, the bead can act as solid phase carrier in assays or sensors. , Compared with a conventional planar carrier like microwell or microarray commonly used in ELISA (enzyme-linked immunosorbent assay), the bead with high surface area to volume ratio (SVR) can be effectively mixed with samples by vortex, which leads to higher sensitivity and shorter reaction time. , In addition, over the past decades, many considerable encoding techniques have been developed, and the beads with unique codes can form suspension array, by which high-throughput and multiplex assays with faster detection and less sample are realized. However, an encoded single bead only bears one kind of molecular probe on its surface, posing a challenge for further sample reduction and higher throughput.…”
mentioning
confidence: 99%
“…Therefore, the bead can act as solid phase carrier in assays or sensors. 8,9 Compared with a conventional planar carrier like microwell or microarray commonly used in ELISA (enzyme-linked immunosorbent assay), the bead with high surface area to volume ratio (SVR) can be effectively mixed with samples by vortex, which leads to higher sensitivity and shorter reaction time. 10,11 In addition, over the past decades, many considerable encoding techniques have been developed, and the beads with unique codes can form suspension array, by which high-throughput and multiplex assays with faster detection and less sample are realized.…”
mentioning
confidence: 99%